1984
DOI: 10.1097/00000658-198401000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and Aneurysm Formation in Umbilical Vein Grafts

Abstract: In a series of 756 glutaraldehyde-stabilized umbilical vein grafts implanted over a 7 1/2-year period, aneurysms were identified in seven cases. The earliest aneurysm was seen at 31 months after implantation and the remainder between 43 and 79 months after surgery. Corrective surgery was performed in five cases and succeeded in four. Although definite mechanisms have not been identified, mechanical fatigue, reversal of aldehyde crosslinks, and immunologic factors may be operative. The pathologic changes includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…'2 However, aneurysm formation remains a major concern in all types of biologic material used as arterial substitutes. Although Dardik' claimed retention of the original HUV graft structure for periods as long as four years, aneurysm development within functioning HUV prostheses has been repeatedly reported.6-9 In 1982, Giordano first published 3 cases of dilatation in HUV grafts.6 In 1984, Dardik reported 9 cases of HUV aneurysm formation, 8 Layer' 3 cases, and Hirsch 13 2 cases. In 1985, Boontye'4 described 9 HUV aneurysms and Hafnerl5 5 further aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…'2 However, aneurysm formation remains a major concern in all types of biologic material used as arterial substitutes. Although Dardik' claimed retention of the original HUV graft structure for periods as long as four years, aneurysm development within functioning HUV prostheses has been repeatedly reported.6-9 In 1982, Giordano first published 3 cases of dilatation in HUV grafts.6 In 1984, Dardik reported 9 cases of HUV aneurysm formation, 8 Layer' 3 cases, and Hirsch 13 2 cases. In 1985, Boontye'4 described 9 HUV aneurysms and Hafnerl5 5 further aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…When the results of these two series are combined, the incidence of GTUV aneurysms rises from 14% (5 of 34 grafts) at 2 to 4 years to 53% (7 of 13 grafts) at 4 to 6 years (p = 0.01). Cranley et al) 8 have recently reported that patent GTUV grafts studied by ultrasonography 5 or more years after implantation had a 44% incidence of frank aneurysm (grade 3 change) and a 34% incidence of diffuse dilation (presumably grade 2 change).…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the processed human um bilical vein is less than expected since fail ures, aneurysms and other problems in com mercially available grafts such as Dardik Bio graft and Mindich Bioflow® have been re ported [34,38,[39][40][41], Although minimized by Dardik et al [42]. they raise serious doubts on the long-term prognosis of the pro cessed human umbilical vein [43].…”
Section: Discussionmentioning
confidence: 99%